CD4 T cell help via B cells is required for lymphopenia-induced CD8 T cell proliferation - Ayasoufi, Katayoun (J Immunol, 2016)
Antibody-mediated lymphoablation is commonly used in solid organ and hematopoietic cell transplantation. However, these strategies fail to efficiently control pathogenic memory T cells and significantly improve long term transplant outcomes. Understanding the mechanisms of T cell reconstitution is critical for enhancing the efficacy of antibody-mediated depletion in sensitized recipients. Using a murine analog of anti-thymocyte globulin (mATG) in a mouse model of cardiac transplantation, we previously showed that peritransplant lymphocyte depletion induces rapid memory T cell proliferation and only modestly prolongs allograft survival. We now report that T cell repertoire following depletion is dominated by memory CD4 T cells. Additional depletion of these residual CD4 T cells severely impairs the recovery of memory CD8 T cells after mATG treatment. The CD4 T cell help during CD8 T cell recovery depends on the presence of B cells expressing CD40 and intact CD40/CD154 interactions. The requirement for CD4 T cell help is not limited to the use of mATG in heart allograft recipients, and is observed in non-transplanted mice and after CD8 T cell depletion with mAb instead of mATG. Most importantly, limiting helper signals increases the efficacy of mATG in controlling memory T cell expansion and significantly extends heart allograft survival in sensitized recipients. Our findings uncover the novel role for helper memory CD4 T cells during homeostatic CD8 T cell proliferation and open new avenues for optimizing lymphoablative therapies in allosensitized patients.